Dynamic response of Pelton runners: Numerical and experimental analysis in prototypes. (September 2020) - Egusquiza, Mònica; Valero, Carme; Valentín, David; Presas, Alexandre; Egusquiza, Eduard
Abstract: Worldwide electricity generation is featured by the growth of intermittent renewable energies. In this context, hydropower plays a fundamental role because it provides flexibility to the power grid and ensures its stability. The new grid requirements have led hydropower units to working under a wider range of loads and with more start/stop sequences. Pelton turbines are the most suitable for high heads and have a large regulation capacity. In operation, the runner is impinged by high-speed water jets, and, thus, subjected to strong pulsating forces. As a consequence, the structure presents large deformations and high stresses, especially on the buckets. This situation can be much aggravated if the frequency and shape of the excitation is resonant with those of the structure. Therefore, the modal response of the turbine must be thoroughly studied and the most dangerous frequencies avoided. In this paper, a detailed analysis of the modal behavior of Pelton turbines is presented. Four prototypes have been studied for such purpose. The first one has been modeled numerically and analyzed experimentally. Following a systematic investigation, the effect on the modal shapes and the frequencies of the different parts comprising the turbine has been evaluated. The single bucket and the whole runner have been studied. Finally, another turbine installed in the same power plant has been analyzed to determine the effect of the mechanical design on the frequencies. In addition, two prototypes belonging to other power plants have been studied to see the effects of the hydrodynamic design on the modal behavior.